2020
DOI: 10.1186/s13046-019-1504-5
|View full text |Cite|
|
Sign up to set email alerts
|

TRIM6 promotes colorectal cancer cells proliferation and response to thiostrepton by TIS21/FoxM1

Abstract: Background: Tripartite motif-containing proteins (TRIM) play a crucial role in carcinogenesis. Little attention has been focused on the possible functions of TRIM6 on carcinogenesis. Methods: The expression levels of TRIM6 were assessed in colorectal cancer (CRC) samples. TRIM6 expression was knocked down in CRC cell lines, and subjected to Cell counting kit-8 (CCK-8), bromodeoxyuridine (BrdU) incorporation and cell cycle assays. Immunoprecipitation and proteomics analysis was performed to identify potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 37 publications
5
26
0
Order By: Relevance
“…TRIM6 functioned as an E3-ubiquitin ligase to destabilize TIS21 during colorectal cancer progression. 10-13 STUB1 was verified as binding target of TRIM6 in this study through Co-IP analysis, and TRIM6 contributed to ubiquitination-mediated degradation of STUB1 in breast cancer cells. STUB1 was also verified as E3 ligase to participate in protein homeostasis involved in neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…TRIM6 functioned as an E3-ubiquitin ligase to destabilize TIS21 during colorectal cancer progression. 10-13 STUB1 was verified as binding target of TRIM6 in this study through Co-IP analysis, and TRIM6 contributed to ubiquitination-mediated degradation of STUB1 in breast cancer cells. STUB1 was also verified as E3 ligase to participate in protein homeostasis involved in neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 55%
“… 11 TRIM44 enhanced NF-κB signaling to promote breast cancer progression, 12 and TRIM59 stabilized programmed cell death protein 10 to promote the motility of breast cancer cell. 13 Considering that TRIM6 contributed to embryonic stem cell pluripotency, 9 and promoted cell proliferation of colorectal cancer, 10 the regulatory role of TRIM6 in breast cancer progression was then investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIM6 protein has been reported to promote cell cycle progression and CRC cell proliferation ( 16 ). In the in vitro and in vivo functional assays, we observed that TRIM6 promotes CRC migration.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding its mechanism, TRIM6 functions as a ubiquitin ligase for c-Myc, allowing it to maintain c-Myc at an appropriate level ( 20 ). Recently published data indicate that TRIM6 promotes CRC cell proliferation ( 16 ). This finding indicates the potential function of TRIM6 in carcinogenesis and cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%